2022
DOI: 10.31234/osf.io/g3nqh
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The DBST index - Discrepancy between desired time in bed and desired total sleep time: A pilot study for the possible new sleep index predicting severity of insomnia

Abstract: ObjectivesWe considered the concept of the discrepancy between a patient's desired time in bed (TIB) and total sleep time (TST), which we termed the DBST. DBST can be used to easily assess a patient’s thoughts on their desired TST and dysfunctionally long TIB. This study aimed to explore whether the DBST can predict the severity of insomnia or dysfunctional beliefs regarding sleep among the general population.MethodsA total of 374 members of the general population participated in this e-survey study. The parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 22 publications
(30 reference statements)
0
7
1
Order By: Relevance
“…The DBST index seems related to the dysfunctional beliefs about sleep. Our previous studies [11][12][13] showed a correlation between the DBST index and rating scales for measuring dysfunctional beliefs about sleep. Although the severity of insomnia is the most powerful predictor of the DBST index, dysfunctional beliefs about sleep may also have an effect on it.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The DBST index seems related to the dysfunctional beliefs about sleep. Our previous studies [11][12][13] showed a correlation between the DBST index and rating scales for measuring dysfunctional beliefs about sleep. Although the severity of insomnia is the most powerful predictor of the DBST index, dysfunctional beliefs about sleep may also have an effect on it.…”
Section: Discussionmentioning
confidence: 92%
“…The desired TIB can be determined by asking, "From what time to what time do you wish to sleep?" The DBST index is calculated as "desired TIB hours-desired hours of TST" [12]. According to a previous report [11], the DBST index is one of the components predicting insomnia severity in the general population, along with depression, preoccupation with sleep, and dysfunctional beliefs about sleep.…”
Section: Concept 2: Discrepancy Between Desired Time In Bed and Desir...mentioning
confidence: 99%
See 1 more Smart Citation
“…We previously reported that the DBST index may be an index for insomnia severity [14,15]. Among the general population [14], the DBST index was significantly correlated with insomnia severity or preoccupation with sleep.…”
Section: Discrepancy Between the Desired Time In Bed And Desired Tota...mentioning
confidence: 91%
“…The DBST index refers to the discrepancy between one's desired total hours in bed and one's desired hours of total sleep [14,15]. One of the most popular misbeliefs of patients with insomnia is that the longer the sleeping time, the better it is for health.…”
Section: Discrepancy Between the Desired Time In Bed And Desired Tota...mentioning
confidence: 99%